KAMPUNG LAMPION DAN PLANG NAMA JALAN - Sugeng Hadi Purnomo, SH., MH. (JPM17: Jurnal Pengabdian Masyarakat, 2017)
Lanterns are the result of culture and characteristics of the ancient era of Asia, where at that time there is no light bulb as now as a source of lighting that can be made easilyand cheaply. This lampion besides being used as a lighting source can also be used todecorate the village to beautify the atmosphere in the village itself. To change theimage of our dolly localization using lanterns as one way to beautify the formerlocalization dolly located in kelurahan putat jaya. We hope that the existence of thisvillage of lanterns can change the picture of the former localization of the dolly andby conducting the training of making the lanterns can help them to be more positivethinking in looking for income from making the lanternKeywords : Putat Jaya, Lampion, , Plang Nama Jalan, Ex Dolly